Remote Sensing of Antarctic Sea Ice with Coordinated Aircraft and Satellite Data Acquisitions - Nghiem, Son; Busche, Thomas Edmund; Kraus, Thomas; Bachmann, Markus; Kurtz, Nathan; Sonntag, John; Woods, John; Ackley, Stephen; Xie, Hongjie; Maksym, Ted; Tinto, Kirsteen; Rack, Wolfgang; et al. (IGARSS 2018 - 2018 IEEE International Geoscience and Remote Sensing Symposium, 2018)
Remote sensing of Antarctic sea ice is required to characterize properties of the vast sea ice cover to understand its long-term increase in contrast to the decrease of Arctic sea ice. For this objective, the OIB/TanDEM-X Coordinated Science Campaign (OTASC) was successfully conducted in 2017 to obtain contemporaneous and collocated remote sensing data from NASA's Operation IceBridge (OIB) and the German Aerospace Center (DLR) TanDEM-X Synthetic Aperture Radar (SAR) system at X band together with Sentinel-1 and RADARSAT-2 SARs at C band in conjunction with WorldView satellite spectral sensors, surface measurements, and field observations. The Weddell Sea and the Ross Sea were two primary regions while SAR data were also collected over six other regions in the Southern Ocean. Satellite SAR data included both polarimetric and interferometric capabilities to infer snow and sea ice information in three dimensions (3D), while OIB/P-3 aircraft data include snow radar together with altimeter data for snow and sea ice observations in 3D over the Weddell Sea. Across the Ross Sea, IcePOD and AntNZ/York-University flights were carried out together with satellite SAR data acquisitions.